Characterization and Application of Hydroxyapatite From Chicken Egg Shell with Green Template as a Potential Drug Delivery System - Irwansyah, Ferli Septi; Nurizal, Abshar Fathur Rochman; Hadisantoso, Eko Prabowo; Zain, Shariffuddin Bin Md (Jurnal Kimia Valensi, 2024)
Hydroxyapatite (HAp) is a calcium phosphate biomaterial widely studied in the medical field because of its good biocompatibility properties. This study aims to identify the effect of increasing variations in banana peel template concentration on the characteristics of hydroxyapatite so that it has the potential as a drug delivery system. This study includes the characterization and application of the potential of the hydroxyapatite drug delivery system with the addition of variations in the concentration of green template. Then, hydroxyapatite was characterized using X-ray diffraction (XRD) and a surface area analyzer (SAA). This study's results indicate that adding a banana peel template affects the characteristics of hydroxyapatite. The higher the template concentration, the smaller the crystallite size, pore size, pore volume, and surface area, but the degree of crystallinity is greater. The results showed that the characterization of hydroxyapatite K15% with a crystal size of 34.73 nm, a degree of crystallinity of 89%, a pore size of 7.2178 nm, a surface area of 30.111 m2/g, and a pore volume of 0.1145 cc/g. The results of the study of the potential of the drug delivery system obtained a loading efficiency value of 67% for ibuprofen. However, the ibuprofen release process results at time intervals tend to be unstable.